Chinese women and the cyberspace - Kuah-Pearce, Khun Eng, 1958- (ICAS publication series. Edited volumes, 2008)
This edited book examines how Chinese women negotiate the Internet to empower themselves and the tensions and conflicts that arise out of this use.